Tuberculosis in wildfowl--Tuberculosis in a Wigeon and a Shelduck from Britain - Harrison, Jeffery G (Wildfowl, 1957)
Any sick or dead duck found in the close season is sure to be interesting. They are not often found, but in the past two years I have obtained two. The first, an adult drake Wigeon (1), was swimming on a loch on South Ronaldsay in the Orkneys on 3 June 1955, a very wasted and sick bird, which was killed and found to be suffering from advanced avian tuberculosis in both lungs, both shoulder joints and the air sacs. The tubercule organism was cultured and found to be a typical smooth avian strain, sensitive to streptomycin. The Shelduck had a gross tuberculous peritonitis and the right lung heavily infected. The organism was cultured and proved to be a typical avian strain. While doing the post-mortem, a heavy infestation of intestinal worms was noted. It is interesting to speculate whether the bird's resistance was lowered by its heavy parasitic burden, so that it subsequently developed tuberculosis. These two appear to be the only proved cases in wild ducks in Europe.